ALiEM Blog and Podcast Watch: Procedures in Emergency Medicine - Joshi, Nikita (West J Emerg Med, 2017)
INTRODUCTION: The WestJEM Blog and Podcast Watch presents high-quality, open-access educational blogs and podcasts in emergency medicine (EM) based on the ongoing Academic Life in EM (ALiEM) Approved Instructional Resources (AIR) and AIR-Professional series. Both series critically appraise resources using an objective scoring rubric. This installment of the Blog and Podcast Watch highlights the topic of procedure emergencies from the AIR Series. METHODS: The AIR Series is a continuously building curriculum that follows the Council of Emergency Medicine Residency Directors’ (CORD) annual testing schedule. For each module, relevant content is collected from the top 50 Social Media Index sites published within the previous 12 months, and scored by eight AIR board members using five equally weighted measurement outcomes: Best Evidence in Emergency Medicine (BEEM) score, accuracy, educational utility, evidence based, and references. Resources scoring ≥30 out of 35 available points receive an AIR label. Resources scoring 27–29 receive an “honorable mention” label if the executive board agrees that the post is accurate and educationally valuable. RESULTS: A total of 85 blog posts and podcasts were evaluated in June 2016. This report summarizes key educational pearls from the three AIR posts and the 10 Honorable Mentions. CONCLUSION: The WestJEM Blog and Podcast Watch series is based on the AIR and AIR-Pro series, which attempts to identify high-quality educational content on open-access blogs and podcasts. This series provides an expert-based, post-publication curation of educational social media content for EM clinicians, with this installment focusing on procedure emergencies within the AIR series.